2011
DOI: 10.5737/1181912x2129197
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the experience of compassion fatigue in clinical oncology nurses

Abstract: Compassion fatigue (CF) is "debilitating weariness brought about by repetitive, empathic responses to the pain and suffering of others" (LaRowe, 2005, p. 21). The work performed by oncology nurses, and the experiences of the people they care for, place oncology nurses at high risk for CF (Pierce et al., 2007;Ferrell & Coyle, 2008 Aneshensel, Pearlin, Mullan, Zarit, and Whitlatch (1995) that considers caregivers' stress in four domains provided the study framework (see Figure 1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(133 citation statements)
references
References 18 publications
8
80
0
9
Order By: Relevance
“…In addition to positive changes, there are negative changes in nurses. Perry et al () found negative effects in life outside of work for nurses who experienced STS. They often become insensitive and indifferent to family and their environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to positive changes, there are negative changes in nurses. Perry et al () found negative effects in life outside of work for nurses who experienced STS. They often become insensitive and indifferent to family and their environment.…”
Section: Discussionmentioning
confidence: 99%
“…My advisor, along with her colleagues, explored the phenomena of compassion fatigue in oncology nurses. [3233] It was her background in the broader topic of nurses’ grief, specifically in the field of oncology, which made her a suitable knowledgeable critic. Similarly, I had access to several colleagues, including a nurse practitioner who specialized in palliative care and wrote her thesis on vicarious traumatization, as well as four of my oncology nursing colleagues who I also consulted.…”
Section: Methodsmentioning
confidence: 99%
“…This is a two-edged sword. On one hand, this leads to the provision of quality care and effective treatment for the patients, but on the other hand, leads to the vulnerability of CF in nurses (Perry, Toffner, Merrick, & Dalton, 2011). Klimecki, Leiberg, Ricard, and Singer (2014) investigated the effect of sympathy and compassion training on cerebral functioning flexibility and concluded that sympathy training increases adverse sympathetic and emotional responses.…”
Section: Discussionmentioning
confidence: 99%